THE PRINCIPAL'S STRATEGY IN MAINTAINING THE QUALITY OF EDUCATION DURING THE COVID 19 PANDEMIC AT PAUD ADINDA TEBING TINGGI - Armanila Armanila; Hotni Sari Harahap; Hasnah Siahaan; Hilda Zahra Lubis (Proceeding International Seminar of Islamic Studies, 2022)
During the current COVID-19 pandemic, school principals need good leadership skills to master competencies as school principals in building quality education. On this basis, researchers conducted research on the Principal's Strategy in Maintaining Education Quality During the COVID 19 Pandemic at PAUD ADINDA, Tebing Tinggi City. The type of research used is descriptive research with a qualitative approach, the research subject is the principal and the object of research is the quality of education, which is located in ADINDA PAUD in the road Tuanku Imam Bonjol Lk, Tambangan Hulu Village, Padang Hilir District, Tebing Tinggi City, North Sumatra. The data collection techniques used include observation, interviews, and documentation. Meanwhile, the data analysis used Miles and Huberman, namely da a reduction (data reduction), data display (data presentation), and conclusion drawing/verification (drawing conclusions). The results of the study indicate that there is an awareness of the importance of the quality of education in schools during the Covid-19 pandemic, which is followed by the implementation of the various roles of school principals in maintaining the quality of education, by providing the best service to students, parents and the community.Keywords: Principal, Quality, Early Childhood Education.